Risk factors associated with high linezolid trough plasma concentrations. (12th June 2016) - Morata, L.; De la Calle, C.; Gómez-Cerquera, J. M.; Manzanedo, L.; Casals, G.; Brunet, M.; Cobos-Trigueros, N.; Martínez, J. A.; Mensa, J.; Soriano, A.
ABSTRACT: Aim : The major concern of linezolid is the adverse events. High linezolid trough serum concentration (Cmin ) has been associated with toxicity. The aim of this study was to analyze factors associated with high Cmin . Methods : Main clinical characteristics of 104 patients treated with 600 mg/12 hours of linezolid were retrospectively reviewed. Samples were obtained just before the next dose after at least three doses and within the first 8 days of treatment. High Cmin was considered when it was >8 mg/L. Univariate and multivariate analysis were performed. Results : 34.6% patients had a Cmin >8 mg/L, and they were older and had more frequently an estimated glomerular filtration by MDRD <40 mL/min. There were more patients co-treated with rifampin in the group with low Cmin . The only factor independently associated with Cmin >8 was the renal function. Patients with an eGF < 40 mL/min had significantly higher Cmin than those with eGF > 80 mL/min (OR: 4.273) and there was a trend towards a high Cmin in patients with eGF between 40-80 mL/min (OR: 2.109). Conclusions : High Cmin were frequent, especially in patients with MDRD <40 mL/min. Therapeutic drug monitoring could be useful to avoid toxicity in patients with renal dysfunction.